Rentabilidad económica del local comercial Las Golondrinas periodo 2021 – 2022 - Cruz Moreira, Eugenia Elizabeth (2023)
The Las Golondrinas commercial premises are dedicated to the marketing of lingerie, bazaar items, personalized alterations, ice cream parlours, fast foods, etc. It has a problem that worries its ability to measure the profitability of its operations during the 2021-2022 period. Currently, it does not have the necessary tools to calculate this very important indicator for small and medium-sized companies. The lack of an adequate registration system for sales at the Las Golondrinas commercial premises is a difficulty that has been affecting the company for some time. The fact that all sales are written down in a notebook makes it difficult to get an overview of sales values and therefore makes it difficult to measure the profitability of the business. The purpose of this case study is to carry out an analysis of the profitability of the Las Golondrinas commercial premises located in the city of Babahoyo, province of Los Ríos, through techniques and practices learned in the curriculum, a comparison of the values obtained will also be made. within the analysis of the profits that cover the period 2021 and 2022, giving the respective conclusions. In this case study, the root cause analysis method was used to identify the factors that influence the profitability of the Las Golondrinas commercial premises, located in the Babahoyo canton. This approach allowed us to examine in detail the origin of the problems that affect the business's sales, which have hindered its growth